Biopsychosocial Determinants of Dental and Oral Health Behavior in Elementary School Children in Ponorogo, Indonesia: Application of Health Belief Model - Fahma Widya Kusumawardhani (Journal of Health Promotion and Behavior, 2020)
Background: Based on Basic Health Research in 2018, the proper brushing teeth behavior in children in Indonesia was 2.8%. The Elementary School period is an important stage for developing the behavior of maintaining dental and oral health in children (students). This study aimed to analyze the bio psychosocial determinants of the behavior of maintaining dental and oral health in elementary school children in Ponorogo by implementing the theory of Health Belief Model.Subjects and Method: This was a cross-sectional study conducted in Ponorogo, East Java, Indonesia, from January to February 2020. A sample of 200 students from 25 elementary schools was selected by simple random sampling. The dependent variable was dental and oral health behavior. The independent variables were knowledge, teacher’s role, attitude, perceived susceptibility, perceived seriousness, perceived benefit, perceived barrier, cues to action, self-efficacy, and school. The data were collected by questionnaire. The data were analyzed by a multilevel multiple logistic regression run on Stata 13.Results: Dental and oral health behavior in elementary school students increased with good knowledge (OR= 8.73; 95% CI= 2.18 to 34.95; p= 0.002), strong teacher’s role (OR= 3.99; 95% CI= 1.17 to 13.65; p= 0.027), positive attitude (OR= 6.45; 95% CI= 1.73 to 24.04; p= 0.005), strong perceived susceptibility (OR= 7.81; 95% CI= 2.12 to 28.78; p= 0.011), high perceived seriousness (OR= 6.62; 95% CI= 1.93 to 22.69; p= 0.003), weak perceived barrier (OR= 0.18; 95% CI= 0.05 to 0.72; p = 0.015), big perceived benefit (OR= 7.78; 95% CI= 1.80 to 33.56; p= 0.006), strong cues to action (OR= 3.95; 95% CI= 1.12 to 13.91; p= 0.032), and strong self-efficacy (OR= 4.99; 95% CI= 1.38 to 18.05; p=0.014 ). Elementary schools had contextual effect on the dental and oral health behavior with ICC= 14.14%.Conclusion: The behavior of maintaining dental and oral health in elementary school students is affected by good knowledge, strong teacher’s role, high perceived susceptibility, high perceived seriousness, weak perceived barrier, big perceived benefit, high cues to action, and strong self-efficacy. The school has a contextual effect on the behaviour of maintaining dental and oral health in students.Keywords: the behaviour of maintaining dental health, health belief model.Journal of Health Promotion and Behavior (2020), 5(2): 135-146https://doi.org/10.26911/thejhpb.2020.05.02.08